The ark plan - Martin, Laura (New York : Harper, 2016)
A century and a half after cloned dinosaurs forced humans to move into underground compounds, Sky discovers a clue to the whereabouts of her long-missing father and ventures above ground on a quest that has the potential to save the world.
School Library Journal, May 2016
Horn Book, April 2017
Bulletin (Center for Children's books), May 2016
5.4
3-6
790L
Keywords: Friendship -- Juvenile fiction; Dinosaurs -- Juvenile fiction; Survival -- Juvenile fiction; Friendship -- Fiction; Dinosaurs -- Fiction; Survival -- Fiction; Action and adventure fiction